Carbon nanowires made by the insertion-and-fusion method toward carbon–hydrogen nanoelectronics. Issue 13 (9th March 2023) - Liu, Fu; Wang, Qingqing; Tang, Yuchao; Du, Wan; Chang, Weiwei; Fu, Zewei; Zhao, Xinluo; Liu, Yi
Abstract : Carbon nanowires can be made via the insertion-and-fusion of short carbon chains inside carbon nanotubes, and carry H adatoms that can tune the electronic and magnetic properties of carbon chains upon the varied H positions in C–H nanoelectronics. Abstract : Carbon nanowires (CNWs), long linear carbon chains encapsulated inside carbon nanotubes, exhibit sp hybridization characteristics as one of one-dimensional nanocarbon materials. The research interests on CNWs are accelerated by the successful experimental syntheses from the multi-walled to double-walled until single-walled CNWs recently but the formation mechanisms and structure–property relationships of CNWs remain poorly understood. In this work, we studied the insertion-and-fusion formation process of CNWs at an atomistic level using ReaxFF reactive molecular dynamics (MD) and density functional theory (DFT) calculations with particular focus on the hydrogen (H) adatom effects on the configurations and properties of carbon chains. The constrained MD shows that short carbon chains can be inserted and fused into long carbon chains inside the CNTs due to the van der Waals interactions with little energy barriers. We found that the end-capped H atoms of carbon chains may still remain as adatoms on the fused chains without C–H bond breaking and could transfer along the carbon chains via thermal activation. Moreover, the H adatoms were found to have critical effects on the distribution of bond length alternation as well as the energy level gaps and magnetic moments depending on the varied positions of H adatoms on the carbon chains. The results of ReaxFF MD simulations were validated by the DFT calculations and ab initio MD simulations. The diameter effect of the CNTs on the binding energies suggest that multiple CNTs with a range of appropriate diameters can be used to stabilize the carbon chains. Different from the terminal H of carbon nanomaterials, this work demonstrated that the H adatoms could be used to tune the electronic and magnetic properties of carbon-based electronic devices, opening up the door toward rich carbon–hydrogen nanoelectronics.